Surgical ergonomics among ophthalmologists at Alsaim Eye Hospital, Wad Madani, Sudan: a clinical audit - Imtinan Yousif; Khawla Jibreel; Mehera Mohammed (Discover Public Health)
Abstract Background Ergonomics is the design of efficiency and comfort in the working environment. Neglecting surgical ergonomics might lead to early retirement and decreased productivity. This study aimed to assess ophthalmologists’ surgical ergonomic practices and compared them to expert ophthalmologists’ recommendations published by the Royal College of Ophthalmologists. Methods In this audit cycle, we sent an anonymous online pretested questionnaire via Google Form to all ophthalmologists and residents at Alsaim Eye Hospital, aiming for total coverage. Based on the literature, we designed a questionnaire that inquired about the participants’ demographics, time spent in the operating room, prior reading about ergonomics, history of musculoskeletal (MSK) pain and injuries, history of exercise, and frequency of adherence to our standard. Descriptive statistics were generated by SPSS version 27, and the Chi-square test was used to check for possible associations. Results The response rate was 51%. Most of the participants were residents 51.6%. Prominent respondents were females (74.2%) and within the 31–40-year age group. Almost half of them had no routine exercise. Nevertheless, most participants (83.9%) reported that they had not read about surgical ergonomics previously. 48.4% of the participants experienced work-related MSK pain. None of the operation room postures reached the targeted standard, with the highest value (77.3%) for the appropriate seating and the lowest (22.6%) for maintaining a straight back. When calculating the association between years of experience and adherence to the established operating postures, only maintaining proper gaze reached a statistical significance (P value of 0.04). MSK pain was associated with more years of experience (P value of 0.04). Conclusion Work-related MSK pain was prevalent among ophthalmologists, and their posture during surgery did not meet the standard criteria for ergonomic practice. Our recommendations include mandatory ergonomic training to the curriculum and conducting large-scale studies to review the situation in Sudan.